PENGARUH MEDIA SOSIAL TERHADAP EFEKTIFITAS PROMOSI DI UNIVERSITAS PASIR PENGARAIAN - Andi Afrizal, Anita, Yulfita 'Aini, (Jurnal Mahasiswa Prodi Manajemen Fakultas Ekonomi, 2017)
This research aims to to find out the influenze of social media to promotion effectiviness at university of pasir pengaraian. The population in this research were all of the student at university of pasir pengaraian. The sample in this research used aksidental sample, with total 96 people. The analisis data used simple regressionlinear has result 0,902 show the loud relation ship between social media with promotiom effectiveness, aspositive influence. The result coefficient determinasi account that 38,1% as social media has influence towardsocial media promotion effectiveness 38,1% with the residue 61,9% has influence with the other variable. From the result of account hypotheses test show T account more bigger from T table was T account.7,614>1,66123 so the hypotheses show any significant influence social media toward promotion effectivenessbe able accepted.